DM-VLP-Grasp: Diffusion Model-Based Grasp Planning with Visual-Language Pretraining for Unknown Object Manipulation - Li, Changyu; Liu, Gao; Liao, Ruchao; Yu, Linkun; Zhan, Jianguo; Ding, Ning (Informatica, 2025)
This paper proposes an unknown object grasping algorithm (DM-VLP-Grasp) based on diffusion model and visual language pre-training, aiming to improve the grasping performance of robots in complex environments. By improving the visual language pre-training model, the image and text information are integrated to accurately extract the object grasping features; the diffusion model is used to generate a reliable grasping strategy, and efficient grasping is achieved through iterative optimization. On a self-built dataset containing 8000 samples, the results show that the grasping success rate of DM-VLPGrasp reaches 93.6%, and the single strategy generation time is 0.78 seconds, showing high stability and computational efficiency. The grasping stability is measured by the root mean square value (RMS) of the object shaking amplitude and the grasping force fluctuation range, both of which show excellent performance. The experimental results verify the effectiveness and innovation of the algorithm in the unknown object grasping task, and provide a new solution for robot automated grasping.